STRATEGI BERTAHAN HIDUP PEREMPUAN PENJUAL BUAH-BUAHAN (Studi Perempuan di Pasar Raya Padang Kecamatan Padang Barat Kota Padang Propinsi Sumatera Barat) - Irwan, Irwan (Pusat Kajian Humaniora FBS Universitas Negeri Padang, 2015)
This research is inspired by women’s involvement in public sectors with limited resources and access. One of the sectors is fruit selling. Various problems in selling demands the women to find strategies to continue to meet family needs. The purpose of the study is to describe factors that push women to choose selling fruits and their strategies to overcome the problem of income for the family. The theory used is the action actor from Max Weber. This research is qualitative descriptive. Data is collected through observation, interview, and documentation. Based on the results, it can be concluded: 1. Driving factors of women choosing to sell fruits are; a) economic factors; small capital is needed, b) social factors and cultural heritage; the efforts of parents and their relationships with fruit growers, c) seasonal characteristic of the fruits, and d) educational factors; most female fruit sellers are low educated. 2. Survival strategies of the women are; a) having dual income, b) reducing household spending, c) cooperating with fruit growers or agent, d) arisan (collective saving), e) changing the type of fruits sold according to the periods of the fruits, and f) changing the type of goods sold.